Shariah Compliance of Wakalah Concept in Takaful Operation: A Case Study of A Takaful Operation in Malaysia - Nadiah 'Aqilah Mohd Amin; Mohamad Abdul Hamid (Institute for Research and Community Empowerment (LPPM TAZKIA), 2013)
Objective – The main objective of this paper is to focus on wakalah model and its impact in takaful operation and to evaluate the compliance of takaful company with shari’ah principles in applying the wakalah concept.Methods – qualitative method which is based on library research. Reference to many books, articles, proceeding papers, handouts, journals, and internet source regarding wakalah by Etiqa Takaful Berhad.Result–The finding of this research shows that the takaful operation in Etiqa Takaful Berhad relies solely on the role of agents to market and promote their products. The agents shall act in accordance with the agreement signed by both parties as to the duties and work to be done by the agent. Binding agreement between the agent and the principal in Etiqa Takaful Berhad is the Family Takaful Agency Agreement and the General Takaful Agency Agreement.Conclusion –It can be concluded that the agency system should be further strengthened as it has important role in takaful business. Indirectly, it can enhance the development of Islamic finance in Malaysia as well as make it known to the society that it is a good system and can completely replace conventional insurance in this industry.Keywords: Wakalah, Agency System, Takaful, Conventional Insurance